Net effects of soil disturbance and herbivory on vegetation by a re-established digging mammal assemblage in arid zone Australia. (October 2016) - Verdon, Simon James; Gibb, Heloise; Leonard, Steven W.J.
Abstract: Large-scale re-introductions of locally extinct digging mammal assemblages have been implemented at a number of arid zone sites, with the aim of conserving mammal species and restoring ecosystem function. Previous studies have focused on the ways in which foraging pits benefit plants, but the effects of herbivory by digging mammal assemblages are poorly understood. We used a randomised block design with control, procedural control and exclusion plots (n = 10) to experimentally test the net effect of a re-established mammal assemblage of bridled nailtail wallabies, Onychogalea fraenata, greater bilbies, Macrotis lagotis, brush tailed-bettongs, Bettongia penicillata, and burrowing bettongs, Bettongia lesueur, on plants in the Australian arid zone. We found that the re-established mammal assemblage limited natural seedling abundance and consumed transplanted seedlings. Plant composition between treatments did not differ, but perennial forbs and subshrubs, which are known food items of the re-introduced mammals, were most abundant in mammal exclusions. Furthermore, a landscape-scale survey showed that composition in the re-introduction area differed significantly from an adjacent control. When conceptualising the role of mammalian ecosystem engineers in arid environments, negative effects on plants from herbivory and soil disturbance must be considered alongside the better studied processes of nutrient cycling and seedling establishment. Highlights: A re-established digging mammal assemblage reduced seedling abundance Palatable plant functional groups were rarer in the re-introduction area Plant composition differed between the re-introduction area and an adjacent control The trophic effects of ecosystem engineers require consideration